Narrativas de práticas em educação estatística e a agência profissional de professores de matemática - Scarlassari, Nathalia Tornisiello (2021)
This research has as it’s main objective to analyze pedagogical actions that characterize the professional agency of mathematics teachers, by teaching statistics and probability to students in the final years of elementary school. In the search to achieve this, the following central question was outlined: "How to characterize the professional agency of mathematics teachers, from the narratives of their practices, by providing Statistical Education in the final years of elementary school?" To answer this question, it was assumed that the teacher is a producer of knowledge and the methodology adopted is part of qualitative research with a (auto)biographical approach that takes the narratives of themselves as a means of (self)formation according to the studies of Vicentini; Souza; Passeggi (2013); Passeggi (2020). The data consist of narrative interviews (Bolívar et al., 2001) and narratives of practices (Bertaux, 2010) of three mathematics teachers, effective of the municipal network of Valinhos - SP, participants of the Research and Training Group in Mathematics Education (Gifem), which became collaborative over time. Among others, the theoretical contributions that support this study are Freire (1989, 1996), Bolívar et al. (2001), Day (2001), Fullan; Hargreaves (2001), Larrosa (2014, 2018), Nacarato (2014, 2018), Lopes (2008; 2018), Passos (2010), Passeggi (2010; 2011), Cyrino (2017), Cyrino e Paula (2020), Tardif; Lessard (2014); Garfield; Gal (1999). The data allowed us to identify that the narratives have reflexive potential allowing the teacher to resignify their practice. As analyses that occur in the classroom, anxieties and insecurity of the process, as actions that characterize the professional agency occurred from listening to the teacher's voice. The results show that teachers participating in a collaborative group feel empowered to dare differentiated, creative, innovative activities for statistical practices involving and what probability they develop in schools. Find in the collaborative group support of peers and a space for discussion and resignification of their actions. Listening to the student, putting him at the center of the learning process is part of teacher learning and indicates that the teacher is taking over his professional agency. In addition to giving visibility to what happens in the classroom of public schools, the professional trajectories of teachers are presented through biograms that show the power of continuous training, of maintaining learning throughout professional life. The teacher's agency is developing and empowering itself in the active participation in the collaborative group, which contributes to the constitution of individual professional identity at the same time that the group assumes a collective identity. The authorship process (personal self realization) is intrinsically related to the biographical condition assumed by the group members. The key process that legitimizes this authorship is the creative insubordination assumed by the teachers.